Migration, Religion, Gender und Bildung: Beiträge zu einem erweiterten Verständnis von Intersektionalität - Behr, Harry Harun; Kulaçatan, Meltem (transcript, 2020)
This volume focuses on national and international cross-cutting perspectives on gender, flight and migration in connection with education and governmental regulatory measures.